2005
DOI: 10.1146/annurev.ecolsys.36.102403.135635
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History of Poales

Abstract: ▪ Abstract  The predominantly wind-pollinated order Poales includes about one third of all monocot (Angiosperm) species, with c. 20,000 species dominating modern savanna and steppe vegetation. Recent improvements in understanding relationships within the order allow phylogenetic optimizations of habitat preferences and adaptive character states, enabling exploration of the factors that have influenced evolution in this successful order. Poales probably originated in the late Cretaceous in wet nutrient–poor sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
164
1
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 90 publications
6
164
1
7
Order By: Relevance
“…Harms & Mildbraed that occurs in West Africa (Smith and Till 1998). It is included in the order Poales (APG II 2003), close to the Typhaceae (Typha e Sparganium) and Rapateaceae (Bremer 2002, Davis et al 2004, Linder & Rudall 2005, and has traditionally been divided in to three subfamilies: Pitcairnioideae, Tillandsioideae and Bromelioideae, according to the growth habit, the ovary position and fruit and seed morphology (Smith & Downs 1974, 1977. Recent phylogenetic analyses (Crayn et al 2000, Horres et al 2000, Barfuss et al 2005 confirmed the monophyly of the Bromelioideae and Tillandsioideae, but indicated the Pitcairnioideae as a polyphyletic group (Crayn et al 2000, Horres et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Harms & Mildbraed that occurs in West Africa (Smith and Till 1998). It is included in the order Poales (APG II 2003), close to the Typhaceae (Typha e Sparganium) and Rapateaceae (Bremer 2002, Davis et al 2004, Linder & Rudall 2005, and has traditionally been divided in to three subfamilies: Pitcairnioideae, Tillandsioideae and Bromelioideae, according to the growth habit, the ovary position and fruit and seed morphology (Smith & Downs 1974, 1977. Recent phylogenetic analyses (Crayn et al 2000, Horres et al 2000, Barfuss et al 2005 confirmed the monophyly of the Bromelioideae and Tillandsioideae, but indicated the Pitcairnioideae as a polyphyletic group (Crayn et al 2000, Horres et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of septal nectaries in both Xyridaceae and Eriocaulaceae has prompted some authors to speculate that nectaries have evolved de novo in xyrids from ancestors that lacked septal nectaries (Linder and Rudall 2005). Our results show that the nectariferous stylar appendages that characterize some Xyridaceae (except Xyris and Achlyphila: Table 3) are vascularized by dorsal carpellary bundles and have a similar early ontogeny.…”
Section: Floral Anatomy In Xyridaceae 1303mentioning
confidence: 58%
“…Another commelinid family with only three stamens, Mayacaceae (with a single genus, Mayaca), was formerly included among the xyrids (e.g. Linder and Rudall 2005), but a recent molecular analysis (BouchenakKhelladi et al 2014) has tentatively placed Mayacaceae closer to Rapateaceae (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations